(untitled) (Applied Biological Research, 2012)
The present study was aimed to evaluate the effect of post-harvest treatments on the quality and prolongation of post-harvest life of straw berryfruits cv.‘Chandler’. Strawberryfruitsweredipped either in calcium chloride (0.5 or 1.0%) for 1 min. or 0.02% ascorbic acid for 1 min. or fumigated with glacial acetic acid for 5 min. The air-dried treated and untreated fruits were packed in plastic punnets with ordinary cover, LDPE cover and PVC cover and stored at 4°C. The results revealed that physiological weight and decay loss were minimum in fruits treated with 1% CaCl2 and packed in LDPE covered punnets. Total soluble solids increased up to 14th day and thereafter decreased; whereas, acidity decreased in all the treatments with least decrease in fruits packed in punnets with LDPE cover and treated with 1% CaCl2. The treatment also showed lower acid and higher TSS. Thus 1% CaCl2 in combination with punnets having LDPE cover was adjudged as the best treatment for maintaining the quality and improving the shelf life of strawberry.